2021
DOI: 10.1029/2021gl095565
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation of Overshooting Tops in Typhoons Detected by Himawari‐8 Satellite

Abstract: Recent observational studies have also documented a diurnal cycle associated with the upper-level cirrus canopy of tropical cyclone (TC) measured using the infrared (IR) brightness temperature (BT) from satellites (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 37 publications
4
17
0
Order By: Relevance
“…The TC rainband activities from both the control experiment and sensitivity experiment (Figure 6, at 6-h intervals) show an Frontiers in Earth Science frontiersin.org obvious diurnal variation feature, i.e., they are most active in the early morning (Figures 6A,E,H) and the weakest in the evening (Figures 6C,F,J), which is consistent with the finding of previous studies (Kossin 2002;Dunion et al, 2014;Sun et al, 2021). In the control experiment, the outer rainband is in the weakening stage at 30-36 h of integration when the inner-core convective bursts start to be active near the maximum wind speed radius (Figure 3A).…”
Section: Inner-core Structure Of the Typhoonsupporting
confidence: 90%
See 1 more Smart Citation
“…The TC rainband activities from both the control experiment and sensitivity experiment (Figure 6, at 6-h intervals) show an Frontiers in Earth Science frontiersin.org obvious diurnal variation feature, i.e., they are most active in the early morning (Figures 6A,E,H) and the weakest in the evening (Figures 6C,F,J), which is consistent with the finding of previous studies (Kossin 2002;Dunion et al, 2014;Sun et al, 2021). In the control experiment, the outer rainband is in the weakening stage at 30-36 h of integration when the inner-core convective bursts start to be active near the maximum wind speed radius (Figure 3A).…”
Section: Inner-core Structure Of the Typhoonsupporting
confidence: 90%
“…Yaroshevich and Ingel (2013) found that the TC intensification rate in the Northwest Pacific is greater at night than that in the daytime. Sun et al (2021) counted the number of typhoon convection overshooting in satellite images. They found that the deep convection of strong typhoons and rapidly intensifying typhoons are more active than that of general typhoons, and this deep convection phenomenon is usually stronger in the morning and weaker in the evening.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, TS with faster intensification has greater DCC-P and the difference is more remarkable nearer to the storm's center. These results are almost identical with the findings of Sun et al (2021) regarding the OTD in TS.…”
Section: Percentage and Temperaturesupporting
confidence: 90%
“…For instance, it may surge the upper level outflow and stimulate the secondary vertical circulation, therefore enhancing the inner‐core convection (Browner et al., 1977; Dunion et al., 2019; Muramatsu, 1983; O'Neill et al., 2017). Moreover, cold‐cloud pulse or diurnal cycle of convection was found to be positively correlated with TC intensification rate, for example, TC rapid intensification is more likely to occur under strong diurnal pulsing (Lee et al., 2020; Sun et al., 2021; Zhang & Xu, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…• Outward propagating diurnal pulse of precipitation occurs in more than 50% of the tropical cyclone (TC) days, and the frequency increases with TC intensity • Over 50% diurnal pulses develop in the deep convective column, but the deep coupling is reduced at later stage of long-duration pulses • Daily mean precipitation, cloud top, and vertically integrated ice content are markedly elevated in TCs with precipitation pulse for example, TC rapid intensification is more likely to occur under strong diurnal pulsing (Lee et al, 2020;Sun et al, 2021;Zhang & Xu, 2021b).…”
mentioning
confidence: 99%